Dual sensory loss and cognitive impairment: A study in elderly users of gerontological centers in a Galician urban area - Vázquez-Sánchez, Covadonga; Gigirey Prieto, Luz M; Del Oro-Sáez, Carlos P (Optometry and vision science, 2025)
Several studies indicate that dual sensory loss (DSL) is related to cognitive impairment. However, there are still no conclusive data on the role of each individual deficit on cognitive performance when both co-occur in the same person. This study aimed to analyze the possible association between sensory deficit and cognitive impairment in a sample of older adults and whether this association differs in subjects with DSL compared with those with single or no sensory impairment. Participants of this study were older adult users of gerontological centers in an urban area of Galicia (Spain). All subjects underwent visual and auditory screening tests to detect the presence of DSL. The Spanish version of the Mini-Mental State Examination test was used to identify cognitive impairment. Hearing loss was defined according to Ventry and Weinstein's criteria. Visual impairment was defined as a binocular presenting visual acuity <0.5 (20/40). The presence of DSL was established on the basis of the definitions of the single deficits. A total of 534 subjects were examined. Older adults with DSL had the worst results in the Mini-Mental test, and those without sensory impairment had the best. The likelihood of cognitive impairment was greater in older adults with DSL than in those without sensory impairment (odds ratio, 6.06 [3.14 to 11.65]). When only visual impairment was present, the likelihood of cognitive impairment was 3.73 times higher (0.95 to 3.09) than that of subjects with no sensory impairment. Hearing loss alone seems not to be significantly associated with a higher risk of cognitive impairment. The results of this study highlight the importance of continuing research in DSL for the prevention of cognitive impairment, the design of intervention plans, and the optimization of health resources.